2021
DOI: 10.1093/bjs/znaa116
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cell-free mutant KRAS dynamics in patients with pancreatic cancer

Abstract: This prospective observational biomarker trial evaluated the diagnostic and prognostic value of circulating KRAS mutations (cmKRAS) and their perioperative dynamics in patients with resectable pancreatic ductal adenocarcinoma (PDAC). Plasma cmKRAS samples (G12D, G12V, G12R, and G12C) were analysed by droplet digital PCR in 51 patients with resectable PDAC, 20 with advanced PDAC, and 34 with non-malignant pancreatic pathology. Preoperative detection of cmKRAS alone did not correlate with poorer overall and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Alternatively, two studies have not found that pre-operative mut- KRAS detection is an independent risk factor for poor prognosis, but in both studies, the emergence of post-operative mut- KRAS was predictive of poorer outcomes [ 81 , 109 ]. An observational study performing cfDNA testing at the time of resection demonstrated that perioperative variations in the levels of mut- KRAS detected in cfDNA can be a valuable tool for prognostication after curative resection of PDA [ 107 ]. In that study, patients with pre-operative and/or intraoperative detection but no post-operative detection of circulating mutant KRAS had longer OS than those who were entirely KRAS -negative (pre/intra−/post – group) and patients with mut- KRAS detected in cfDNA after surgery (pre/intra+/−/post + group).…”
Section: Cfdna For Pormentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, two studies have not found that pre-operative mut- KRAS detection is an independent risk factor for poor prognosis, but in both studies, the emergence of post-operative mut- KRAS was predictive of poorer outcomes [ 81 , 109 ]. An observational study performing cfDNA testing at the time of resection demonstrated that perioperative variations in the levels of mut- KRAS detected in cfDNA can be a valuable tool for prognostication after curative resection of PDA [ 107 ]. In that study, patients with pre-operative and/or intraoperative detection but no post-operative detection of circulating mutant KRAS had longer OS than those who were entirely KRAS -negative (pre/intra−/post – group) and patients with mut- KRAS detected in cfDNA after surgery (pre/intra+/−/post + group).…”
Section: Cfdna For Pormentioning
confidence: 99%
“…Some have tested post-operative blood or compared pre-operative cfDNA results with post-operative samples (Table 4). Pre-operative detection of KRAS mutation often correlates with poor outcomes, irrespective of resectability (Table 4) [71,81,84,[102][103][104][105][106][107][108][109][110][111]. Alternatively, two studies have not found that pre-operative mut-KRAS detection is an independent risk factor for poor prognosis, but in both studies, the emergence of post-operative mut-KRAS was predictive of poorer outcomes [81,109].…”
Section: Cfdna For Pormentioning
confidence: 99%
“…Liquid biopsy approaches are currently usually based on the analysis of plasma cell free DNA (cfDNA). Most of the (particularly initial) liquid biopsy studies in PDAC focused on the detection of gene variants, especially KRAS mutations [ 76 , 77 , 78 , 79 , 80 ]. However, DNA methylation marks in cfDNA of PDAC patients have also been studied, and they may add clinically relevant information, in particular in combination with genetic analyses.…”
Section: Diagnostic Utility Of Epigenetic Modifications In Pdacmentioning
confidence: 99%